Legal protection of know-how as an element of the digital transformation of the economy of the Republic of Belarus - Lando, Darya D. (Journal of the Belarusian State University. Law, 2021)
The article defines specific features of the right to know-how and refers to its role in the digital economy transformation. The prospects of choosing a model of legal protection for know-how in the Eurasian Economic Union are analysed. The author justifies the need for a legal definition of the nature of the right to know-how in the Civil Code of the Republic of Belarus. It is necessary to introduce a uniform approach in regulating of a contractual transfer of data constituting know-how or the right to know-how. Active development of artificial intelligence technologies raises the question of the appropriateness of protecting the object created by artificial intelligence as know-how. The author suggests taking into account practical aspects while assessing legal amendments concerning know-how.
Keywords: innovation development; artificial intelligence; commercial secrets; trade secrets (know-how); digital economy